2015
DOI: 10.1016/j.jhep.2014.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of aldehyde dehydrogenase 2 by Alda-1 reverses alcohol-induced hepatic steatosis and cell death in mice

Abstract: Pharmacological activation of ALDH2 by Alda-1 reversed alcoholic steatosis and apoptosis through accelerating aldehyde clearance. This study indicates that ALDH2 is a promising molecular target and Alda-1 has therapeutic potential for treating alcoholic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 28 publications
6
59
0
Order By: Relevance
“…Correspondingly, measurements of BEC, the EtOH concentration in the blood after metabolism of consumed EtOH in hPXR males and females treated with or without binge EtOH, were lower in females relative to males. Consistent with this, pharmacological activation of ALDH2 reversed alcoholic steatosis and apoptosis through accelerating acetaldehyde clearance, suggesting that higher ALDH2 levels in hPXR females may provide enhanced protection against alcohol hepatotoxicity (Zhong et al, 2015).…”
Section: Discussionsupporting
confidence: 54%
“…Correspondingly, measurements of BEC, the EtOH concentration in the blood after metabolism of consumed EtOH in hPXR males and females treated with or without binge EtOH, were lower in females relative to males. Consistent with this, pharmacological activation of ALDH2 reversed alcoholic steatosis and apoptosis through accelerating acetaldehyde clearance, suggesting that higher ALDH2 levels in hPXR females may provide enhanced protection against alcohol hepatotoxicity (Zhong et al, 2015).…”
Section: Discussionsupporting
confidence: 54%
“…These results clearly demonstrate that ALDH2 could become a new, emerging target for developing medicines not only for treating cardiovascular diseases but also for other tissues including the liver and brain (Luo, Liu, Ma, & Peng, 2014). Due to the critical role of ALDH2 in serious liver disease (Day et al, 1991;Li, 2000;Li et al, 2001), we expect that small-molecule ALDH2 activators can protect the liver disease caused by alcohol, as recently reported (Zhong et al, 2014) and nonalcoholic substances and in DILI. For instance, alda-1 and its structural analogs could be used to support many East Asian people with the dominant negative mutant (i.e., ALDH2*1/2 or ALDH2*2/2) gene.…”
Section: Translational Research Opportunitiesmentioning
confidence: 79%
“…In fact, Mochly-Rosen and her colleagues identified ALDH2 activators through screening chemical libraries and demonstrated the protective effects of synthetic ALDH2 activators such as alda-1 [N-(1,3-benzodioxol-5-ylmethyl)-2,6-dichlorobenzamide], alda-44, and alda-89, which not only restored the suppressed ALDH2 activity but also significantly protected the heart under I/R condition (Budas, Disatnik, Chen, & Mochly-Rosen, 2010;Chen, Budas, et al, 2008). More recent reports showed that alda-1 is cardioprotective in post-myocardial infarction (Gomes et al, 2015) or in aged mice as well as hepatoprotective against alcoholinduced steatosis and cell death (Zhong et al, 2014). These results clearly demonstrate that ALDH2 could become a new, emerging target for developing medicines not only for treating cardiovascular diseases but also for other tissues including the liver and brain (Luo, Liu, Ma, & Peng, 2014).…”
Section: Translational Research Opportunitiesmentioning
confidence: 99%
“…Nearly, half of the East‐Asian population possessed the genetic mutation which results in the deficiency of ALDH2 activity . Findings from our laboratory and others revealed a beneficial role of ALDH2 in rescuing against certain diseases, such as ischemia heart disease, alcoholic liver disease and stroke, which might be mediated through regulating oxidation stress, apoptosis and autophagy . Nevertheless, the role of ALDH2 in CCl 4 ‐induced chronic liver fibrosis and the underlying mechanisms remains to be further elucidated.…”
Section: Introductionmentioning
confidence: 81%